DIONYSOS SATELLITE OBSERVATORY AND HIGHER GEODESY LABORATORY: HISTORY AND PERSPECTIVES - Marinou, A.; Anastasiou, D.; Papanikolaou, X.; Paradissis, D.; Zacharis, V. (Bulletin of the Geological Society of Greece, 2016)
Dionysos Satellite Observatory and Higher Geodesy Laboratory have been in operation since the 60s and their main objective is to fulfill academic and research needs, determined through the ongoing scientific and technological advance in the field of geodesy. They are involved in all scientific domains related to the determination of earth’s size and figure, as well as its temporal variations. Their field of expertise is Satellite Geodesy, (spanning a wide range of applications like reference systems, tectonic geodesy, etc.), as well as the study of the geoid and earth’s gravity field.